Integrated Management of Nutrients on Growth and Yield of Mungbean - Balo, Sumana; Mukhopadhyay, Dibyendu; Patra, P. S.; Debnath, M. K. (International Journal of Bio-resource and Stress Management, 2026)
A two-year field experiment was conducted in pre-kharif season (Feb-April) during 2021 and 2022 in Randomized Block Design with eight treatments replicated 3 times at the instructional farm of UBKV, West Bengal, India to evaluate the efficiency of integrating organic amendments with reduced doses of chemical P fertilizer on the growth, yield attributes of summer mungbean in an acidic soil. Despite of having high protein content, Mungbean (Vigna radiata L.) productivity was constrained by phosphorus (P) deficiency in widespread acidic soils. Integrated nutrient management (INM) strategies offered a sustainable solution to enhance P availability and crop performance. These treatment included- control (T1), farmer’s practice (T2), state-recommended dose of P (T3), NK+150% of the RD of Phosphorus through SSP (T4), and NK+75% of RD of Phosphorus through SSP+25% Phosphorus through Phosphocompost (T5), NK+75% of the RD of Phosphorus through SSP +25% Phosphorus through Farm Yard Manure (FYM)(T6), NK+75% of RD of Phosphorus through SSP +25% Phosphorus through Vermicompost (T7), or NK+ 75% of the RD of Phosphorus through SSP +25% Phosphorus through Rockphosphate +PSB (T8). Treatment T7 (75% SSP+25% P as Vermicompost) consistently demonstrated superior performance, recording the maximum values for plant height (55.13 cm), branches plant-1 (13.00), pods plant-1 (26.87), test weight (35.50 g), seed yield (10.70 q ha-1) and stover yield (20.3 q ha-1). The treatment T7 was identified as the optimal INM strategy to increas mungbean productivity in acidic soils by improving P use efficiency and soil health, offering a sustainable alternative to sole reliance on inorganic fertilizers.